(untitled) (Bangladesh Journal of Neuroscience, 2026)
Background: Increased body mass index (BMI) has been associated with increased risk of idiopathic intracranial hypertension (IIH). Idiopathic intracranial hypertension is relatively common condition in obese women of reproductive age causing headaches with visual obscuration. Objective: The purpose of the study was to observe the correlation between body mass index (BMI) and visual impairment among patients presenting with idiopathic intracranial hypertension. Methodology: This cross-sectional study was carried out in the Neurology department of National Institute of Neurosciences and Hospital, Dhaka. A total of 100 cases of IIH satisfying the modified Dandy criteria were included in this study. Patients were divided into three groups according to BMI categories corresponding to World Health Organization BMI classification for the people of South Asia with cutoff points: Normal (18.5-22.0 kg/m2), overweight (23-27.5>25 kg/ m2) and Obese (>27 kg/m2). Detailed history, complete neuro-opthalmogical evaluation and necessary investigations were done in every patient. Results: There was no significant difference in baseline demographic data, basic clinical characteristics, associated medications, co-morbidities among 3 groups of patients (p>0.05) but severe visual loss (6/60) was observed in obese among three groups which was statistically significant (p<0.05). There was no significant (p>0.05) difference in association between Log MAR with BMI but significant (p<0.05) difference was found between Normal Vs Obese and Overweight vs Obese in risk of severe visual loss. Conclusion: There is a strong relationship of visual impairment in overweight and obese patients diagnosed as idiopathic intracranial hypertension.